Milman’s History of the Jews: a Real Place with Real People - Mason, Alistair (Studies in church history, 2000)
For English-speaking Protestants in the early nineteenth century, the Holy Land lived in the Bible. In that Land God had done his mighty works, and every name recalled an episode in the history of salvation. Its placenames were as real and resonant to believers as those of their own home district. Chapel-names like Mizpah and Shiloh were not just ‘somewhere in the Old Testament’, as they are to modern readers. Filtered through the anachronism of its readers’ imaginations, and haloed with devotion, the Holy Land was indeed holy.